Easy origami animals - Montroll, John (Mineola, New York Dover Publications, 2014)
"Created by an origami master, these 23 models offer a menagerie of easy-to-fold animals. Figures include birds?a cardinal, parrot, bald eagle, and cranes?and a fox, pig, hippo, elephant, lion, and others. Diagrams illustrate every step of the folding process, and full-color pictures depict the completed models."--Amazon.com.
8 - 12 years
104558
Keywords: Origami -- Juvenile literature; Animals in art -- Juvenile literature; Juvenile works; Juvenile works